Prototype of Hi'Beam-SEE: A Real-Time High-Resolution Single-Event Effects Locating Device for Heavy-Ion Facilities - Liao, Jianwei; Jia, Yanhao; Liao, Shun; Du, Jiangyong; Yang, Haibo; Huang, Ju; Zhang, Honglin; Wei, Xianglun; Zhao, Peixiong; Li, Xianqin; Niu, Xiaoyang; Han, Weijia; et al. (IEEE transactions on nuclear science, 2025)
Integrated circuits (ICs) are widely used in spacecraft and are concerned with the probability of single-event effects (SEEs). To accurately locate the SEE-sensitive area of ICs, we have designed Hi'Beam-SEE for the SEE experiment terminal at heavy-ion facilities. The Hi'Beam-SEE consists of three subsystems: the heavy-ion positioning system (HIP) is responsible for locating the position of each particle in the beam, the single-event detection (SED) system detects the SEEs that occurred in the device under test (DUT), and the online tracking algorithm extracts and reconstructs the position of each particle that triggers SEEs. The beam test with ^{84}\text {Kr}^{18+} particles demonstrates that the HIP can achieve a spatial resolution of 4~μ m in measuring every single particle's position. Also, the SED system can identify SEEs correctly and issue triggers with good timing accuracy. The online tracking algorithm can process 172 frames that contain tracks per second and extract the positions with an accuracy of 3.2~μ m . In addition, it attains a rejection factor of 93.6% while keeping the signal efficiency of 99%. This article will discuss the design and performance characterization of the Hi'Beam-SEE.